2018
DOI: 10.1159/000487448
|View full text |Cite
|
Sign up to set email alerts
|

Does Complement Have a Role in the Pathogenesis of Alopecia Areata?

Abstract: Alopecia areata (AA) is an autoimmune disorder in which immune attack of the anagen follicle causes hair loss in approximately 2% of the population. Although the pathogenesis of AA has not been fully determined, most likely it is mediated by a variety of factors including cellular/humoral immunity and genetic predisposition. Researchers have been interested in the possible role of the complement pathway in AA since the 1970s. Given recent evidence suggesting that complement plays a role in many immunologic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Besides, upregulation of intestinal immune network for IgA, cell adhesion molecules, natural killer cell-mediated cytotoxicity, and complement and coagulation cascades were detected as pathways linked to hair loss. Studies have linked the deposition of C3 at the hair follicle to scarring alopecia such as lupus erythematous, pemphigus vulgaris, and lichen planopilaris [8,21]. However, there is no clear evidence of complement involved in the pathogenesis of AA, although several studies reported deposits of C3 and IgA in perifollicular and at the base of hair follicles [21].…”
Section: Discussion/conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, upregulation of intestinal immune network for IgA, cell adhesion molecules, natural killer cell-mediated cytotoxicity, and complement and coagulation cascades were detected as pathways linked to hair loss. Studies have linked the deposition of C3 at the hair follicle to scarring alopecia such as lupus erythematous, pemphigus vulgaris, and lichen planopilaris [8,21]. However, there is no clear evidence of complement involved in the pathogenesis of AA, although several studies reported deposits of C3 and IgA in perifollicular and at the base of hair follicles [21].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Studies have linked the deposition of C3 at the hair follicle to scarring alopecia such as lupus erythematous, pemphigus vulgaris, and lichen planopilaris [8,21]. However, there is no clear evidence of complement involved in the pathogenesis of AA, although several studies reported deposits of C3 and IgA in perifollicular and at the base of hair follicles [21]. Furthermore, CD8 + T cells, NK cells, and mast cells were signi cantly increased in AA and CLE lesions compared to PSOR lesions, implying that these cells may contribute to hair loss.…”
Section: Discussion/conclusionmentioning
confidence: 99%